ANALISIS KEARIFAN LOKAL PETANI PADI RAMAH LINGKUNGAN DIDESA SUNGAI MANAU KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Alpis, Depit Oktapiandra; Sayamar, Eri '; ', Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Local wisdom is one of the products of culture, local wisdom born of the need for values, norms and rules that serve as model to ferform an action. Local wisdom is a cultural values taught by our ancestors to better appreciate nature and do not be greedy draining.the purpose of this study is to identify the local wisdom that there ever existed and that there is also present in the environment of rice farming. Analyzing the application of lokal wisdom in rice In Village Sungai Manau Subdistrict Kuantan Mudik. Know the strategy of maintaining the local in the cultivation of the rice crops. This study used survey method to determine the respondents use key informan and sample. Methods of sampling done snowball sampling.Samples takeken as many as eleven people. This research uses primary data and secondary data. Data have been obtained in the fileld were analyzed descriptively qualitative. To describe the identification of variable and variable application of lokal wisdom rice farmers used 5W+1H. While to analyze variables by maintaining lokal wisdom analysis SWOT. The results snowed that (1) Identify and (2) Application of lokal wisdom in rice cultivation amounted 66. (3) How to maintain local wisdom of cultivation in particular by addressing new or modern tehnology advances that can change the behavior of farmers who still use traditional as local wisdom is changed by using modern tools. Key words:Localwisdom, identification, farmer.